2013
DOI: 10.1074/jbc.m112.440354
|View full text |Cite|
|
Sign up to set email alerts
|

Reversing the Warburg Effect as a Treatment for Glioblastoma

Abstract: Background: Glioblastoma is the most prevalent brain tumor with the poorest prognosis. Results: Methylene blue enhances oxygen consumption, reduces lactate production, and inhibits glioblastoma cell proliferation. Conclusion: Reversal of the Warburg effect could inhibit glioblastoma cell proliferation. Significance: Modulation of cancer cell bioenergetics and reversal of Warburg effect might provide a novel therapy for glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 49 publications
(53 reference statements)
3
89
0
1
Order By: Relevance
“…Metabolic analysis was performed by NMR analysis of culture medium and cell extracts. The culture media were supplemented with [1][2][3][4][5][6][7][8][9][10][11][12][13] C]glucose to monitor rates of lactate production by the appearance of [3][4][5][6][7][8][9][10][11][12][13] C]lactate in the culture medium, and of Krebs cycle flux by analysis of 13 C labeling patterns of glutamate from the cell extract. H-NMR spectra of cell culture media and cell methanol/water (80%/20%; v/v) extracts were acquired on a 600-MHz NMR Spectrometer (Varian-Agilent Technologies, Santa Clara, CA, USA), using a 3-mm indirect detection probe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic analysis was performed by NMR analysis of culture medium and cell extracts. The culture media were supplemented with [1][2][3][4][5][6][7][8][9][10][11][12][13] C]glucose to monitor rates of lactate production by the appearance of [3][4][5][6][7][8][9][10][11][12][13] C]lactate in the culture medium, and of Krebs cycle flux by analysis of 13 C labeling patterns of glutamate from the cell extract. H-NMR spectra of cell culture media and cell methanol/water (80%/20%; v/v) extracts were acquired on a 600-MHz NMR Spectrometer (Varian-Agilent Technologies, Santa Clara, CA, USA), using a 3-mm indirect detection probe.…”
Section: Methodsmentioning
confidence: 99%
“…7 Several mitochondrial characteristics that distinguish transformed cells from healthy cells have been described, 8 including increased mitochondrial transmembrane electric potential (Dcm), which may result from decreased mitochondrial ATP production under normoxia. 9 Similarly, normal SCs primarily rely on glycolysis for energy supply, although the exact mechanism how this occurs in the presence of oxygen and the relationship between SC metabolism and cell fate control is not yet completely understood. 10 Given the mitochondrial involvement in stemness and differentiation, 11 one can ask whether manipulation of mitochondrial physiology results in an improvement of therapy efficacy.…”
mentioning
confidence: 99%
“…AMPK phosphorylates also the C-terminal residue of another CKI, p27 Kip1 , causing its stabilization (Figure 2) 135 . Likewise, methylene blue (MB)-mediated activation of AMPK reduces expression of cyclins A2, B1 and D1, leading to proliferative arrest 136 . Moreover, activation of AMPK due to mitochondrial dysfunction promotes p53-dependent transcription of the F-box protein archipelago.…”
Section: Pkm2mentioning
confidence: 99%
“…Other articles have also indicated that TMZ resistance is associated with the expression of vascular endothelial growth factor (VEGF) 12 and epidermal growth factor receptor (EGFR) 13 . Changes in EGFR expression by itself activates both MEK and PI3 kinase pathways 14,15 .…”
Section: Introductionmentioning
confidence: 99%